Fundamental of Entrepreneurship ENT300 : Barakallah Bridal Boutique / Nur Amira Bolhassan ... [et al.] - Bolhassan, Nur Amira; Haizam, Nur Zulaikha; Jamal, Siti Hafizzah; Morshidi, Liyana; Rosli, Roslia Hani (2011)
Our company has decided to narrow our business on renting, wedding services and wedding photography after carrying out a wide research on what business prospect we should venture on. We came up with a business plan of partnership and our company will be known as Barakallah Bridal Boutique. The main business of the company is to rent the wedding attires which incorporated Islamic concept in every design. We decided to provide wedding attires which are affordable to the bride and groom depending on their budget. We also provide wedding services such as make up, car decorations and wedding photography. In the process of launching this business plan, we need so take the five major business establishments into consideration which are the operation, administration, finance, management and marketing.